The simultaneous impact of access to credit and cooperative services on cocoa productivity in South-western Nigeria - Ayodeji Damilola Kehinde; Abiodun Akintunde Ogundeji (Agriculture & Food Security, 2022)
Abstract Background Cocoa contributes immensely to Nigeria’s economy; it is about 40% of agricultural exports and it is the main source of livelihood for over 200,000 rural households. However, its productivity has remained low in recent years compared to other cocoa-producing countries such as Cote d’Ivoire and Ghana. Low cocoa productivity is attributed to many factors, which include lack of access to credit and cooperative services. However, empirical information on the simultaneous impact of credit access and membership of cooperative society on cocoa productivity is still very scanty. This paper aims at evaluating the impacts of access to credit service, cooperative service, and simultaneous access to credit and cooperative services on cocoa productivity in South-western Nigeria. Method A multistage sampling procedure was employed to select 300 cocoa farmers for the study. The endogenous switching regression (ESRM) and the inverse probability-weighted regression adjustment (IPWRA) models were used to analyse the data. Results In terms of simultaneous access to credit and cooperative services, age, education, gender, and size of household significantly influence the probability of farmers having simultaneous access to credit and cooperative services. The results of the second stage of the ESRM showed that age, size of household, years of education, and years of experience significantly influence cocoa productivity among farmers who have access to credit and cooperative services. However, age, size of household, size of farm and asset significantly influence the productivity of farmers who do not have access to credit and cooperative services. Average treatment effect on the treated (ATT) revealed that farmers who simultaneously have access to credit and cooperative services achieve significantly higher productivity than farmers who have access to either credit or cooperative services and the set of farmers who do not have access to either credit or cooperative services. Conclusion The study concluded that simultaneous access to credit and cooperative services positively impacted cocoa productivity. Farmers who have simultaneous access to credit and cooperative services achieve significantly higher productivity than farmers who have access to either credit or cooperative services or those that do not have access to these services at all. The study recommends that any agricultural productivity-targeted programmes in Nigeria consider farmers’ simultaneous access to credit and cooperative services.